Cross down - Patterson, James, 1947-; DuBois, Brendan (2023)
"For the first time, John Sampson is on his own. The brilliant crime-solving duo of Washington, DC's, Metro PD and the FBI has a proven MO: Detective Alex Cross makes his own rules. Detective John Sampson enforces them. When military-style attacks erupt, brutally sidelining Cross, Sampson is sent reeling. The patterns are too random, Sampson's friend, his partner, his brother, has told him. Don't trust anyone. As a shadow force advances on the nation's capital, Sampson alone must protect the Cross family, his own young daughter, and every American, including the president"--
Includes excerpt from Cross Out, by the author
Sequel to: Triple cross
Keywords: Sampson, John -- (Fictitious character) -- Fiction; Cross, Alex -- (Fictitious character) -- Fiction; Terrorism -- Prevention -- Fiction; Police -- Washington (D.C.) -- Fiction; African American detectives -- Fiction; Murder -- Investigation -- Fiction; Washington (D.C.) -- Fiction; Thrillers (Fiction); Detective and mystery fiction; Novels